(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vividly, technology has enhanced the world citizen’s lifestyle especially in tourism industry where technology engages in almost every journey’s touchpoint. In airports, technology does not only assist the travellers prior their airport arrivals, it also significantly provides the travelers tremendous convenience during and even post airport experience. It can be said that technology makes travel digitally extraordinary among the technological aids that smoothen passengers’ journey. The Corona Virus Decease (COVID-19) has forever changed the air travelling behaviors. Therefore, technology becomes a crucial tool to facilitate travelers, avoiding infectious risks from close contacts during the travelling journey. Amid COVID-10 situation, airport passengers do not only demand purely on service quality provided by airport and airline staffs, but the demand for beneficial technological facilities, in terms of safety and security, during their airport journeys is rather significant. This article examined the factors influencing airport technology selections in each service touchpoint of Suvarnabhumi Airport based on the survey of 400 airport users employing structured questionnaires. The literature reviews together with the quantitative data were statistically analyzed to interpret the results. Finally, the results indicated 9 factors significantly influencing airport technology selections namely price, rapidness, convenience, culture differences, self-image, trust, airline information provision, environmental negative impact, and technological knowledge.